2003
DOI: 10.1038/sj.npp.1300031
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Metabolic Hypofunction and Neurochemical Deficits after Chronic Intermittent Exposure to Phencyclidine: Differential Modulation by Antipsychotic Drugs

Abstract: Numerous human imaging studies have revealed an absolute or relative metabolic hypofunction within the prefrontal cortex, thalamus and temporal lobes of schizophrenic patients. The former deficit correlates with cognitive deficits and negative symptoms, whereas the latter correlates with positive symptomologies. There is also general consensus that schizophrenia is associated with decreased parvalbumin expression in the prefrontal cortex. Since the drug phencyclidine can induce a psychosis resembling schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
176
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(188 citation statements)
references
References 66 publications
11
176
1
Order By: Relevance
“…Certainly, no one animal protocol can effectively model a disease as complex and heterogeneous as schizophrenia, and previous reports (Pantelis et al, 1999) suggest that individuals with schizophrenia can demonstrate impairment on multiple aspects of cognition, including some non-EDS problems, an effect not addressed by our rodent model. However, the face validity of our model is augmented by previous reports of schizophrenia-like pathology, such as decreased parvalbumin expression (Abdul-Monim et al, 2007) and cortical metabolic hypofunction (Cochran et al, 2003) following PCP administration. Future research should determine whether differential pharmacological effects are replicated in another recently developed neurodevelopmental rodent model of schizophrenia, neonatal treatment with the neurotoxin MAM (methylazoxymethanol), which has been demonstrated to produce impairments in attentional set shifting (Featherstone et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Certainly, no one animal protocol can effectively model a disease as complex and heterogeneous as schizophrenia, and previous reports (Pantelis et al, 1999) suggest that individuals with schizophrenia can demonstrate impairment on multiple aspects of cognition, including some non-EDS problems, an effect not addressed by our rodent model. However, the face validity of our model is augmented by previous reports of schizophrenia-like pathology, such as decreased parvalbumin expression (Abdul-Monim et al, 2007) and cortical metabolic hypofunction (Cochran et al, 2003) following PCP administration. Future research should determine whether differential pharmacological effects are replicated in another recently developed neurodevelopmental rodent model of schizophrenia, neonatal treatment with the neurotoxin MAM (methylazoxymethanol), which has been demonstrated to produce impairments in attentional set shifting (Featherstone et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, we employed the well-validated subchronic phencyclidine (PCP)-administration paradigm (Jentsch and Roth, 1999;Cochran et al, 2003;Egerton et al, 2005;Abdul-Monim et al, 2006, 2007 to produce enduring cognitive deficits similar to those observed in schizophrenia (Javitt and Zukin, 1991). This permitted us to examine treatment effects of classical and second-generation antipsychotics that have different profiles and activity at multiple neurotransmitter receptors, including dopamine (DA) D 2 , 5-HT 2A , and 5-HT 6 .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated reduced density of parvalbumin immuno reactive neurons in the hippocampus and M1 (motor area 1) region of the frontal cortex following sub-chronic PCP treatment in the rat [3]. It has also been shown that chronic intermittent administration of PCP decreases parvalbumin mRNA expression in the prefrontal cortex of rats, and that this reduction can be reversed by clozapine but not haloperidol [11].…”
Section: Introductionmentioning
confidence: 96%
“…Repetitive NMDA-R antagonist treatment in animals produce more persistent effects on stereotypy and locomotor activity, as well as enduring cognitive deficits and neurochemical changes that resemble more accurately the alterations observed in schizophrenia (Jentsch and Roth, 1999;Morris et al, 2005;Mouri et al, 2007). For example, the initial hypermetabolism, observed after acute NMDA-R antagonist exposure, is followed by a decrease in metabolic activity in the PFC, as well as within structures of the auditory system, and the reticular nucleus of the thalamus (Cochran et al, 2003). Repetitive PCP decreases dopamine in the dorsolateral prefrontal cortex, prelimbic cortex, and cingulate cortex, but not in supplementary motor area (Jentsch and Roth, 1999).…”
Section: Introductionmentioning
confidence: 97%